The fire safety awareness in residential village house / Ahmad Faris Yusuf and Irwan Mohammad Ali - Yusuf, Ahmad Faris; Mohammad Ali, Irwan (2023)
In residential, fire safety is a major problem, especially in village dwellings where fire events can have disastrous results owing to restricted access to emergency services and resource limitations. This study intends to evaluate the degree of fire safety knowledge among village home occupants and to pinpoint any possible areas for development. To collect information on residents' awareness of fire safety measures, current safety practices, and perceptions of fire hazards, the study used a mixed-methods approach that combines surveys and interviews. The study also examines the success of community-wide fire safety education initiatives currently in place and how they affect local people' readiness. The findings emphasize both the positive and negative aspects of village house dwellers' fire safety awareness, including knowledge gaps. Fire safety education is critical for all levels of society, particularly those who live in residential settings such as village cottages. The majority of village house dwellers are unconcerned about the safety of their dwellings and rely entirely on the fire department if their homes catch fire. First and first, in order to raise public awareness, the definition of the term "fire safety" must be defined. Fire safety is the planning or construction of infrastructure to lessen the danger of fire or to prevent the spread of a larger fire.